From innovation to clinic: Emerging strategies harnessing electrically conductive polymers to enhance electrically stimulated peripheral nerve repair - Rajiv Borah; Daniel Diez Clarke; Jnanendra Upadhyay; Michael G. Monaghan (Materials Today Bio)
Peripheral nerve repair (PNR) is a major healthcare challenge due to the limited regenerative capacity of the nervous system, often leading to severe functional impairments. While nerve autografts are the gold standard, their implications are constrained by issues such as donor site morbidity and limited availability, necessitating innovative alternatives like nerve guidance conduits (NGCs). However, the inherently slow nerve growth rate (∼1 mm/day) and prolonged neuroinflammation, delay recovery even with the use of passive (no-conductive) NGCs, resulting in muscle atrophy and loss of locomotor function. Electrical stimulation (ES) has the ability to enhance nerve regeneration rate by modulating the innate bioelectrical microenvironment of nerve tissue while simultaneously fostering a reparative environment through immunoregulation. In this context, electrically conductive polymer (ECP)-based biomaterials offer unique advantages for nerve repair combining their flexibility, akin to traditional plastics, and mixed ionic-electronic conductivity, similar to ionically conductive nerve tissue, as well as their biocompatibility and ease of fabrication. This review focuses on the progress, challenges, and emerging techniques for integrating ECP based NGCs with ES for functional nerve regeneration. It critically evaluates the various approaches using ECP based scaffolds, identifying gaps that have hindered clinical translation. Key challenges discussed include designing effective 3D NGCs with high electroactivity, optimizing ES modules, and better understanding of immunoregulation during nerve repair. The review also explores innovative strategies in material development and wireless, self-powered ES methods. Furthermore, it emphasizes the need for non-invasive ES delivery methods combined with hybrid ECP based neural scaffolds, highlighting future directions for advancing preclinical and clinical translation. Together, ECP based NGCs combined with ES represent a promising avenue for advancing PNR and improving patient outcomes.